2020
DOI: 10.1016/j.eujim.2020.101144
|View full text |Cite
|
Sign up to set email alerts
|

Laughter and humour for personal development: A systematic scoping review of the evidence

Abstract: Introduction: The accessibility of laughter and humour make them attractive choices for selfcare, and integrative medicine. There is a growing body of literature, but both fields are fragmented and the overall evidence has not been systematically reviewed. The relationship between health and personal development is increasingly recognized. This review scopes the evidence for laughter and humour interventions from the perspective of their potential benefits on personal development. Methods: A systematic scoping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 158 publications
0
32
0
3
Order By: Relevance
“…Similarly, it might be of interest to examine the differential effects of humor, seen as a predominantly cognitive process, and laughter as a physical behavior on outcomes associated with chronic pain, as they do not necessarily occur together. 52 There indeed is some evidence that also laughter only therapies might be effective in increasing well-being and also in reducing pain for different patient populations. 31,53 In the present study, patients often laughed in the training sessions, especially in module 1 (allowing yourself to laugh), but frequency and duration of laughter were not documented or measured individually, which would be necessary to build evidence for the benefit of laughter.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it might be of interest to examine the differential effects of humor, seen as a predominantly cognitive process, and laughter as a physical behavior on outcomes associated with chronic pain, as they do not necessarily occur together. 52 There indeed is some evidence that also laughter only therapies might be effective in increasing well-being and also in reducing pain for different patient populations. 31,53 In the present study, patients often laughed in the training sessions, especially in module 1 (allowing yourself to laugh), but frequency and duration of laughter were not documented or measured individually, which would be necessary to build evidence for the benefit of laughter.…”
Section: Discussionmentioning
confidence: 99%
“…Laughter and humour can have wide-ranging Biological, Psychological, Social and socio-economic, Environmental, and Behavioural (BPSE-B) benefits on personal development throughout the lifecycle [ 17 ]. Although laughter and humour are often viewed as spontaneous social activities, both can be trained and self-induced solo activities.…”
Section: Discussionmentioning
confidence: 99%
“…Laughter is a natural, free, innate behaviour associated with a range of health outcomes across the lifecycle [ 17 ]. A meta-analysis of ten randomised controlled trials (RCTs) of laughter and humour interventions showed they significantly decreased adult depression, anxiety, and improved sleep quality [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are also more than 350 research papers (Nilsen, n.d.). Most critical reviews of the research appeared within the last two decades (Banas, Dunbar, Rodriguez, & Liu, 2010;Berk, 2001aBerk, , 2001bBerk, , 2002Berk, , 2004aBerk, , 2004bBerk, , 2014Gonot-Schoupinsky et al, 2020;Jonas, 2019;Martin, 2001Martin, , 2003Martin & Ford, 2018;McGhee, 1999McGhee, , 2010Nijholt, 2020;Provine, 2000;Raskin, 2008;Rindfleisch, 2018;Savage, Lujan, Thipparthi, & DiCarlo, 2017;Segrist & Hupp, 2015). Those reviews furnish a somewhat sobering, realistic assessment of the evidence to pinpoint what we know and what we don't know (but would like to know).…”
Section: Review Of Research On Humor and Laughtermentioning
confidence: 99%
“…With the isolation and the loss of loved ones and colleagues, jobs, income, homes, and mental and physical health, humor can at least provide a coping strategy for the trauma and grieving so many educators and students have experienced (Klein, 1989(Klein, , 1998(Klein, , 2019Mork, 2019). The psychophysiological benefits of humor can be very therapeutic (Berk, 2001a(Berk, , 2002(Berk, , 2004a(Berk, , 2015Gonot-Schoupinsky, Garip, & Sheffield, 2020;Martin, 2001;Martin & Ford, 2018;McGhee, 2010;Rindfleisch, 2018). But I digress.…”
Section: Introductionmentioning
confidence: 99%